Effect of Slaking Water Properties to Lime Quality - KILIC, OZEN (Asian Journal of Chemistry, 2010)
The slaking of lime is important for its use in a number of industrial applications. There are normally a number of factors that can influence the rate, reactivity of the hydration of lime, which include, amongst others, production and storage conditions and the constitution of the water used in the slaking process. In this study, the influence of slaking water properties to lime quality has been investigated. It was found that soft burnt lime during slaking process dramatically increases its surface area and also reactivity. In the slaking experiments of limes were used water, distilled water and distilled water mixtures, with sugar, NaCl, ethonol and methonol.